Polyhydroxybutyrate-producing cyanobacteria from lampenflora: The case study of the “Stiffe” caves in Italy - Djebaili, Rihab; Mignini, Amedeo; Vaccarelli, Ilaria; Pellegrini, Marika; Spera, Daniela M.; Del Gallo, Maddalena; D’Alessandro, Anna Maria (Frontiers in Microbiology, 2022)
The present study aimed to study the green formation lampenflora of “Stiffe” caves to evaluate their suitability as an isolation source of cyanobacteria useful for PHAs production. The cave system was chosen as the sampling site due to its touristic use and the presence of high impact illuminations. The biofilms and the mats of the illuminated walls were sampled. Samples were investigated by 16s rRNA analysis and culturable cyanobacteria isolation. The isolated strains were then screened for PHAs production under typical culturing and nutritional starvation. Cultures were checked for PHAs accumulation, PHB presence (infrared spectroscopy), and pigments production. The 16s metabarcoding highlighted a considerable extent of the pressure exerted by anthropogenic activities. However, the isolation yielded eleven cyanobacteria isolates with good PHAs (mainly PHB) producing abilities and interesting pigments production rates (chlorophyll a and carotenoids). Under normal conditions (BG110), the accumulation abilities ranged from 266 to 1152 ng mg dry biomass-1. The optimization of bioprocesses through nutritional starvation resulted in a 2.5-fold increase. FT-IR studies established the occurrence of PHB within PHAs extracted by cyanobacteria isolates. Results comparison with standard strains underlined good production rates. For C2 and C8 strains, PHAs accumulation rates under starvation were higher than Azospirillum brasilense and similar to Synechocystis cf. salina 192. The present study broadened the knowledge of the microbial communities of mats and biofilms on the lightened walls of the caves. These findings suggested that these structures, which are common in tourist caves, could be used to isolate valuable strains before remediation measures are adopted.